Vasospasm in Cerebral Inflammation - Michael Eisenhut (International Journal of Inflammation)
All forms of cerebral inflammation as found in bacterial meningitis, cerebral malaria, brain injury, and subarachnoid haemorrhage have been associated with vasospasm of cerebral arteries and arterioles. Vasospasm has been associated with permanent neurological deficits and death in subarachnoid haemorrhage and bacterial meningitis. Increased levels of interleukin-1 may be involved in vasospasm through calcium dependent and independent activation of the myosin light chain kinase and release of the vasoconstrictor endothelin-1. Another key factor in the pathogenesis of cerebral arterial vasospasm may be the reduced bioavailability of the vasodilator nitric oxide. Therapeutic trials in vasospasm related to inflammation in subarachnoid haemorrhage in humans showed a reduction of vasospasm through calcium antagonists, endothelin receptor antagonists, statins, and plasminogen activators. Combination of therapeutic modalities addressing calcium dependent and independent vasospasm, the underlying inflammation, and depletion of nitric oxide simultaneously merit further study in all conditions with cerebral inflammation in double blind randomised placebo controlled trials. Auxiliary treatment with these agents may be able to reduce ischemic brain injury associated with neurological deficits and increased mortality.